The implications for Ireland - Teeling, John T. (Statistical and Social Inquiry Society of Ireland, 1989)
As is now common practice this paper uses "mergers" and "takeovers" interchangeably. Takeover activity is a normal part of business activity, though you would hardly think so to read the lurid reports in the popular press. A mythology has grown up in relation to merger activity. This is heightened by the emergence of a vocabulary of emotive terms which mean mundane things in practice but sound great - "Golden Parachutes" instead of "Redundancy Payments"; "White", "Black" or "Grey Knights" meaning friendly, hostile or unknown (mentioned suitor; "Dawn Raids" and "Saturday Night Specials" meaning a quick purchase of a large block of shares, while the "Pacman Defence" means simply turning the tables on the bidder. "Asset Strippers", "Raiders", and "Predators" are investors wishing to make assets earn their keep to make them "Sweat" to use the modern terminology. Takeover specialists have achieved international stardom or notoriety depending on your viewpoint. Is all of this deserved? I think not. Merger activity is usually conducted in the public eye. Opportunities arise for quick profits which sometimes tempt individuals into unethical and/or illegal behaviour. But this should not disguise the true nature of takeovers which are an essential and necessary part of the restructuring and industrial renewal process by which the economy initiates and responds to change. Takeover is only one form of investment activity. If a company expands by building a new factory which is so cost effective that it wipes out competition, then the investor is applauded. An innovator who introduces a new technology which leads to closures, bankruptcies and job losses among competitors is looked up to as a captain of industry and a wealth creator. Yet the investor who uses takeovers as a means of restructuring an industry is often pictured as a "Predator" or "Vulture".
Symposium on the International Dimension in Corporate Mergers and Acquisitions
Read before the Society, 2 March, 1989
Keywords: Mergers; Takeovers; 314.15